Pseudomonas aeruginosa microcolonies in coronary thrombi from patients with ST-segment elevation myocardial infarction - Hansen, Gorm Mørk (2018)
Chronic infection is associated with an increased risk of atherothrombotic disease and direct bacterial infection of arteries has been suggested to contribute to the development of unstable atherosclerotic plaques. In this study, we examined coronary thrombi obtained in vivo from patients with ST-segment elevation myocardial infarction (STEMI) for the presence of bacterial DNA and bacteria. Aspirated coronary thrombi from 22 patients with STEMI were collected during primary percutaneous coronary intervention and arterial blood control samples were drawn from radial or femoral artery sheaths. Analyses were performed using 16S polymerase chain reaction and with next-generation sequencing to determine bacterial taxonomic classification. In selected thrombi with the highest relative abundance of Pseudomonas aeruginosa DNA, peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) with universal and species specific probes was performed to visualize bacteria within thrombi. From the taxonomic analysis we identified a total of 55 different bacterial species. DNA from Pseudomonas aeruginosa represented the only species that was significantly associated with either thrombi or blood and was >30 times more abundant in thrombi than in arterial blood (p<0.0001). Whole and intact bacteria present as biofilm microcolonies were detected in selected thrombi using universal and P. aeruginosa-specific PNA-FISH probes. P. aeruginosa and vascular biofilm infection in culprit lesions may play a role in STEMI, but causal relationships remain to be determined.